(untitled) - Hirsch, Scott (Indianapolis, Ind., 2006)
This practical guide from two certified Pro Tools experts begins where most other Pro Tools books leave off--it's like having a high-level, hands-on studio session with your very own seasoned audio pros! Jump in anywhere and discover the professional techniques and tricks you need to get recordings right the first time, every time
Keywords: Pro Tools,Digital audio editors,Pro tools,Biên tập âm thanh kỹ thuật số